Free tissue transfer for trophic ulcer complicating leprosy - Bhatt Yogesh; Panse Nikhil; Vyas Kinnari; Patel Gunjan (Indian Journal of Plastic Surgery)
Plantar ulceration is the commonest disability in leprosy and occurs in about 10 to 20% of leprosy patients. Various loco-regional flaps have been described for reconstruction of trophic ulcers; however, very large defects are not amenable to local flaps and free flaps form one of the important treatment options. We present a case of a post Hansen′s trophic ulcer over the forefoot managed using a radial artery forearm free flap. Debridement of the osteomyelitic bone, removal of the bony prominences, coverage by a well-vascularised tissue, end-to-side arterial anastomosis, use of anterior tibial as the recipient vessel and good postoperative compliance in foot care on the part of the patient gave us good results.